PREDICTING THE POPULATION TREND OF THE RHESUS MACAQUE (Macaca mulatta) AT SON TRA PENINSULA, DA NANG CITY - Vinh Thanh, Nguyen; Tuan Anh, Nguyen; Dinh Duy, Nguyen; Van Linh, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2026)
The Rhesus macaque (Macaca mulatta) population at Son Tra Peninsula, Da Nang city, is experiencing conflicts with both residents and tourists, manifested in aggressive foraging behaviors and frequent incursions into residential areas. This study evaluated whether the rhesus macaque population on the Son Tra Peninsula has approached the carrying capacity of the habitat and assessed its projected trajectory under different snaring scenarios. In this study, a transect survey method was used to estimate the number of individuals in the macaque troops and the total number of individuals in the entire Son Tra Peninsula area. The age and sex structure of the troops was also recorded using this method. Population size, age–sex structure, group composition, and relevant ecological and demographic parameters were entered into Vortex 10 to simulate population trajectories over the next 50 to 100years. The results show that under current conditions, with a total of 1487 individuals observed, the Rhesus macaque population in Son Tra has the potential to increase to approximately 1922 individuals. If the rate of illegal snaring consistently exceeds10% of the total population at that time, the population size will begin to decline and gradually become extinct within 100 years.